2018
DOI: 10.1016/j.jped.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric chronic patients at outpatient clinics: a study in a Latin American University Hospital

Abstract: This study evaluated a large population in a Latin American hospital and suggested that early adolescents with chronic diseases required many appointments, multiple specialties and hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
0
24
1
3
Order By: Relevance
“…The result of the present study was different from that of research on MD/PhD programs in Canada and the United States, which found that men were the predominant gender (9,10,13,20). (5) Results are presented as n (%), HRQL-health-related quality of life, STI-sexually transmitted infection.…”
Section: ' Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The result of the present study was different from that of research on MD/PhD programs in Canada and the United States, which found that men were the predominant gender (9,10,13,20). (5) Results are presented as n (%), HRQL-health-related quality of life, STI-sexually transmitted infection.…”
Section: ' Discussioncontrasting
confidence: 97%
“…Previous research has shown that personal, professional, and educational characteristics, ratings of overall satisfaction, physical/psychological stress, and professional issues after undergraduate, fellowship, and residency training are different around the world (5,6,(16)(17)(18). However, to the best of our knowledge, simultaneous analysis of these data has not been carried out among health professionals in Latin America, after master's, doctoral, and post-doctoral degree completion.…”
mentioning
confidence: 99%
“…PCDs were classified according to the duration of the disease (over three months), and the diagnosis was established by the physician's scientific knowledge, valid methods or tools based on professional standards, and/or diagnostic classification criteria. 1,6 The 10th Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) was also systematically evaluated to characterize the main PCD diagnoses. 6,21 We assessed the following 23 pediatric specialties, according to the electronic data system: Allergy & Immunology, Cardiology, Endocrinology, Gastroenterology, Genetics, Hematology, Hematopoietic Cell Transplantation, Hepatology, Infectious Diseases, Nephrology/Renal Transplantation, Neurology, Nutrology, Oncology, Orthopedics, Palliative and Pain Care, Pediatric Surgery/Liver Transplantation, Pulmonology, Psychiatry, Rheumatology, and others (Adolescent Care, Preterm Care, and Pediatric Teaching Clinic).…”
Section: Methodsmentioning
confidence: 99%
“…This fact is due to the advancements in medical diagnosis, with new technologies and specific treatments for different illnesses and comorbidities. [1][2][3][4][5][6][7][8][9][10][11] Of note, child and adolescent populations with chronic health disabilities requiring highly complex medical care have been increasingly followed-up in tertiary centers. A French study with individuals younger than 14 years old showed that 3.3% of patients had long-term conditions, and 1.4% had complex chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation